2018
DOI: 10.1002/wea.3259
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of links between regional climate change and precipitation extremes over India

Abstract: A significant change in the precipitation pattern over India has been reported in previous studies. This change includes an increase in heavy precipitation and a decrease in light and/or moderate precipitation. This study examines the possible link between these changes and regional climate conditions, using regional surface temperature and Vertically Integrated Moisture Transport (VIMT) records. It is reported that precipitation extremes during the southwest (SW) monsoon season show coherent variability with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…This technique can help to understand the linkages between the climate change and the environment. As we know that the climate change has affected the precipitation patterns worldwide, there are increases in heavy precipitation and low-to-moderate precipitation is showing a decline, resulting in frequent flooding and droughts (Mishra, Panda, and Rafiq 2016;Mishra et al 2018). The impact of this precipitation change has much more impacts on the cryosphere as changes in the snowfall over these mountains are directly affecting the glacier mass balance.…”
Section: Introductionmentioning
confidence: 99%
“…This technique can help to understand the linkages between the climate change and the environment. As we know that the climate change has affected the precipitation patterns worldwide, there are increases in heavy precipitation and low-to-moderate precipitation is showing a decline, resulting in frequent flooding and droughts (Mishra, Panda, and Rafiq 2016;Mishra et al 2018). The impact of this precipitation change has much more impacts on the cryosphere as changes in the snowfall over these mountains are directly affecting the glacier mass balance.…”
Section: Introductionmentioning
confidence: 99%
“…The UofT-CCSM4 simulations were produced in its coupled configuration with a horizontal resolution of 1 • . For the analyses reported herein, WRF-CROCO was driven by three distinct GCM simulations, including one for the PI climate and two for the MH climate, the latter being forced by the PMIP4-mandated concentrations of greenhouse gases (GHGs) and orbital parameters (Otto-Bliesner et al, 2017). One of the MH experiments employs a preindustrial land surface and a vegetation prescribed to PI values, and it therefore differs from the PI only with regards to the orbital configuration and trace gas concentrations; the other MH experiment also incorporates GS boundary conditions by including vegetation, soil, and lake modifications over Africa and Arabia.…”
Section: Model Descriptions and Experimental Designmentioning
confidence: 99%
“…Krishnan et al (2016) showed that, the enhancement of such deep localized convection, leading to heavy rainfall events, are more likely to happen in an atmosphere with weak vertical shear (Romatschke and Houze 2011). Increased variability of low-level monsoon westerlies (Mishra et al 2018;Roxy et al 2017) and warming of north Arabian sea lead to increased moisture supply and thus enhance such events (Roxy et al 2017). By examining the changes in the distribution of moderate and heavy monsoon precipitation in Historical and GHG, only simulations Krishnan et al (2016) have shown that along with increase of atmospheric moisture the decrease of easterly vertical shear of the SAM circulation is also pivotal for favouring localized heavy rainfall over the Indian region (Fig.…”
Section: Observed Changes and Their Attributionmentioning
confidence: 99%